1996
DOI: 10.1111/j.1476-5381.1996.tb15208.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo profile of SB 206553, a potent 5‐HT2C/5‐HT2B receptor antagonist with anxiolytic‐like properties

Abstract: 4 At similar doses (2-20 mg kg-', p.o.) SB 206553 increased total interaction scores in a rat social interaction test and increased punished responding in a rat Geller-Seifter conflict test. These effects are consistent with the possession of anxiolytic properties. 5 SB 206553 also increased suppressed responding in a marmoset conflict model of anxiety at somewhat higher doses (15 and 20 mg kg-', p.o.) but also reduced unsuppressed responding. 6 These results suggest that SB 206553 is a potent mixed 5-HT2c/5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
173
1
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(195 citation statements)
references
References 31 publications
(42 reference statements)
18
173
1
3
Order By: Relevance
“…The progressive ratio procedure is used to assess the motivational value of a reinforcer: If a drug increases the reinforcing value of the Ensure solution, the mice respond at higher breakpoint values; if a drug decreases the reinforcing value of the Ensure solution, the mice respond at lower breakpoint values. For example, the 5-HT 1B/2C receptor agonist mCPP, which produces hypophagia in many assays (e.g., Kennett and Curzon 1988;Kennett et al 1996), significantly decreased the breakpoint value for Ensure solution (Fig. 4) without altering response rates in the progressive ratio assay, as previously reported (Ward et al 2008).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The progressive ratio procedure is used to assess the motivational value of a reinforcer: If a drug increases the reinforcing value of the Ensure solution, the mice respond at higher breakpoint values; if a drug decreases the reinforcing value of the Ensure solution, the mice respond at lower breakpoint values. For example, the 5-HT 1B/2C receptor agonist mCPP, which produces hypophagia in many assays (e.g., Kennett and Curzon 1988;Kennett et al 1996), significantly decreased the breakpoint value for Ensure solution (Fig. 4) without altering response rates in the progressive ratio assay, as previously reported (Ward et al 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Any dose of drug that produced changes in the autoshaping-operant procedure was also examined in the progressive ratio procedure. In addition, m-chlorophenylpiperazine (mCPP), a serotonin agonist that produces hypophagia in many assays (e.g., Kennett and Curzon 1988;Kennett et al 1996) and decreases the breakpoint value for Ensure in mice (Ward et al 2008), was tested as a positive control of a compound that decreases breakpoint responding.…”
mentioning
confidence: 99%
“…Abercrombie et al, 1989;Thierry et al, 1976). 5-HT2C receptors have also been implicated in anxiety (Kennett et al, 1996(Kennett et al, , 1997. Thus, it is increasingly important to understand the role of 5-HT/DA interactions in depression, anxiety, and their treatments.…”
Section: Depression/anxietymentioning
confidence: 99%
“…Although drugs interacting acutely with alpha-adrenergic receptors or dopaminergic receptors modulate 8-OH-DPAT-induced hypothermia in mice (Bill et al 1991;Durcan et al 1991), this has been shown not to be the case for 8-OH-DPAT-induced hypothermia in rats (Millan et al 1997). However, if mianserin or ketanserin treatment had modified 8-OH-DPATinduced hypothermia or forepaw treading in the current study, it would have been necessary to address the potential involvement of alpha-adrenergic receptors or 5-HT 2C receptors by investigating the effect of chronic administration of the alpha-1 antagonist prazosin or the selective 5-HT 2C receptor antagonist SB 206553 (Kennett et al 1996) on these 5-HT 1A receptor mediated behaviors. In the absence of an effect of either ketanserin or mianserin on 8-OH-DPAT-induced hypothermia or forepaw treading, we did not investigate this further.…”
Section: Discussionmentioning
confidence: 84%